2017
DOI: 10.1111/bju.14051
|View full text |Cite
|
Sign up to set email alerts
|

Multiple growth periods predict unfavourable pathology in patients with small renal masses

Abstract: While overall growth rate was not predictive of pathology favourability, there was a positive association between the number of positive growth periods and unfavourable pathology. The number of positive growth periods may be a potential parameter for malignant potential in patients undergoing active surveillance for small renal masses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Optimal management of patients on AS would appear to require a good understanding of growth kinetics, pathological details, and risk–benefit analysis. The previously held dogma of using linear growth rate as a guide for the aggressiveness of a tumour has been challenged recently and again put into question by this study . The Delayed Intervention and Surveillance for Small Renal Masses (DISSRM) study showed that there was a higher growth rate in patients who had delayed intervention compared with those on AS, but there was no significant association ( P = 0.15) .…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Optimal management of patients on AS would appear to require a good understanding of growth kinetics, pathological details, and risk–benefit analysis. The previously held dogma of using linear growth rate as a guide for the aggressiveness of a tumour has been challenged recently and again put into question by this study . The Delayed Intervention and Surveillance for Small Renal Masses (DISSRM) study showed that there was a higher growth rate in patients who had delayed intervention compared with those on AS, but there was no significant association ( P = 0.15) .…”
mentioning
confidence: 84%
“…Jang et al. provide insight into this need by evaluating the number of growth periods over time as a risk factor for renal masses under surveillance. They retrospectively reviewed renal masses that were initially <4 cm at diagnosis and were followed for a variable time period before undergoing surgical therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While GR is not an adequate surrogate for determining malignant potential, the number of positive growth periods may be more predictive of adverse pathology. Jang et al identified 124 patients who underwent surgery for SRMs (mean initial tumor size 3.4 cm SD 2.5) and had multiple pre-operative imaging studies (median 2 imaging studies) over a mean pre-operative surveillance time of 0.8 year [21]. Patients were divided into two groups based on favorable pathology (defined as benign tumors, chromophobe RCCs, or low grade pT1-2 RCC) and unfavorable pathology (defined as any high grade RCC or locally advanced, low grade pT3-4 RCC); some of these tumors were upstaged after pathologic examination.…”
Section: Tumor Size and Growth Ratementioning
confidence: 99%
“…They noted a difference in the number of positive growth periods between favorable and unfavorable tumors, with unfavorable tumors being more likely to have at least 2 growth periods during observation compared to the favorable pathology group (p = 0.02), while there was no significant difference in GR between the two groups (p = 0.07). Furthermore, the unfavorable pathology group had a smaller proportion of zero "positive growth" periods [21]. This can be explained by "immunoediting" in which cancer cells' growth and elimination by immune cells are in a state of equilibrium, until mutations occur that allow cancer cells to enter the escape phase of tumor growth unchecked by the immune system [22].…”
Section: Tumor Size and Growth Ratementioning
confidence: 99%